2020
DOI: 10.1149/2162-8777/aba67b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Structural and Optical Properties of Ga2O3Thin Films Grown on m-plane Sapphire Substrates by Low-Pressure MOCVD

Abstract: In this paper, Ga2O3 films were grown on m-sapphire substances at different temperatures of 600 °C, 700 °C and 800 °C by low pressure MOCVD. By changing the temperature, the crystal phase change of the Ga2O3 thin films grown on the m-sapphire substrates were studied. The effects of temperature on structural characteristics, surface morphology and optical properties of the films were studied systematically. XRD results indicated that the mixture of α-phase and β-phase Ga2O3 films were obtained on the m-sapphire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Alongside the anisotropy, bulk β-Ga 2 O 3 suffers from cleavage which is another drawback of β-phase. Moreover, homoepitaxy in (100) orientation is susceptible to high density of twin boundaries which limits the electrical properties like conductivity and mobility.…”
Section: Crystal Structures and Their Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside the anisotropy, bulk β-Ga 2 O 3 suffers from cleavage which is another drawback of β-phase. Moreover, homoepitaxy in (100) orientation is susceptible to high density of twin boundaries which limits the electrical properties like conductivity and mobility.…”
Section: Crystal Structures and Their Physical Propertiesmentioning
confidence: 99%
“…Deposition of ( 201) oriented β-Ga 2 O 3 films was achieved on sapphire (0001), MgO (111) and homoepitaxial β-Ga 2 O 3 ( 201) single crystals [111,180,181]. However, β-Ga 2 O 3 (100) growth was performed on various substrates such as GaN (0001)/sapphire, MgAl 6 O 10 (100), gadolinium gallium garnet (Gd 3 Ga 5 O 12 ) (110), KTaO 3 (100) and SrTiO 3 (100) [115,[182][183][184][185]. The ( 201) orientation was also reported on MgO (110) substrate [186].…”
Section: Mocvdmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the diffraction peak at 64.4°c omes from α-Ga 2 O 3 (30-30) plane, and the remaining diffraction peaks are related to β-Ga 2 O 3 , consistent with our previous research. 38 Interestingly, the diffraction peak intensities related to β-Ga 2 O 3 and α-Ga 2 O 3 plane decreases, on the contrary, the intensity of β-Ga 2 O 3 (−402) diffraction peak at 38.1°increases as the growth pressure increases (as can be seen in Fig. 3b).…”
Section: Resultsmentioning
confidence: 83%
“…6,15,26 In our previous work, we deposited and investigated a series of Ga 2 O 3 films on different substrates. We analyzed the influence of growth temperature or growth pressure on the crystal phase and orientation of Ga 2 O 3 films deposited on m− or r-plane sapphire substrates, 27,28 and found that the increase in growth pressure can supress the growth rate and grain size of β-Ga 2 O 3 films on sapphire substrate. 29,30 We also investigated the Ga 2 O 3 films deposited on the epi-GaN/sapphire substrates, and it still grew preferentially along the (−201) crystal plane family at higher growth temperatures.…”
mentioning
confidence: 99%